Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (Nht) Berbantuan Media Interaktif Berbasis Animasi terhadap Motivasi dan Hasil Belajar Siswa UpTD SMP Negeri 1 Kokop - Sofiatun, Sofiatun; Wijayanti, Rica; Nuraini, Nuraini (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This study aims to reviw student learning motivation and student learning achievement tests using Numbered Head Together (NHT) learning assisted by interactive media based on animation the research method used is the Lilierfrors method assisted by Microsoft Excel. In terms of the teacher’s ability, and can increase the ability of student in learning data processing while the purpose of this research is to find out student motivation questionnaires and student learning achievement tests, this reseachis in the from of quantitative research the subject of this research is class VII-A students at UPTD SMP NEGERI 1 KOKOP the data collection instrument used on learning motivation and student response test sheets which were very positive, where 98% of students expresses their enjoyment of learning using the Numbered Heads Together (NHT) cooperative learning model through interactive media based on animation achievement tests. Positive and understand 99% of this study it is stromgly application of the Numbered Heads Together (NHT) cooperative learning model can increase student learning VII-A UPTD SMP NEGERI 1 KOKOP in data processing material.